Caribbean reefs of the Anthropocene: Variance in ecosystem metrics indicates bright spots on coral depauperate reefs. (21st July 2020) - Lester, Sarah E.; Rassweiler, Andrew; McCoy, Sophie J.; Dubel, Alexandra K.; Donovan, Mary K.; Miller, Margaret W.; Miller, Scott D.; Ruttenberg, Benjamin I.; Samhouri, Jameal F.; Hay, Mark E.
Abstract: Dramatic coral loss has significantly altered many Caribbean reefs, with potentially important consequences for the ecological functions and ecosystem services provided by reef systems. Many studies examine coral loss and its causes—and often presume a universal decline of ecosystem services with coral loss—rather than evaluating the range of possible outcomes for a diversity of ecosystem functions and services at reefs varying in coral cover. We evaluate 10 key ecosystem metrics, relating to a variety of different reef ecosystem functions and services, on 328 Caribbean reefs varying in coral cover. We focus on the range and variability of these metrics rather than on mean responses. In contrast to a prevailing paradigm, we document high variability for a variety of metrics, and for many the range of outcomes is not related to coral cover. We find numerous "bright spots, " where herbivorous fish biomass, density of large fishes, fishery value, and/or fish species richness are high, despite low coral cover. Although it remains critical to protect and restore corals, understanding variability in ecosystem metrics among low‐coral reefs can facilitate the maintenance of reefs with sustained functions and services as we work to restore degraded systems. This framework can be applied to other ecosystems in the Anthropocene to better understand variance in ecosystem service outcomes and identify where and why bright spots exist. Abstract : Dramatic coral loss has significantly altered Caribbean reefs, and coral loss is predicted to result in broad declines in ecosystem services. We evaluate 10 key ecosystem metrics, relating to a variety of different reef services and functions, using data from 328 Caribbean reefs varying in coral cover. Our results document high variability for a variety of metrics and suggest that "bright spots"—sites where these metrics are comparatively high (i.e., 90th percentile)—can occur where coral cover is low. Notably, bright spots for many metrics related to fish communities are more likely at medium than high coral cover sites.